Yield Potential and Yield Stability in Durum Wheat using Crop Wild Relative Crosses, and Participatory Assessment of Moroccan Farmers Preferences - El Haddad, Noureddine; Sanchez-Garcia, Miguel; Visioni, Andrea; Verma, Ramesh Pal Singh; Abderrazek, Jilal; Agrawal, Shiv Kumar; Kilian, Benjamin; Bassi, Filippo (2024)
This presentation took place during the African Plant Breeders Association Conference held at Mohammed VI Polytechnic University (UM6P) in Benguerir, Morocco, from October 23rd to 26th, 2023. It outlines the key achievements in advancing yield potential and stability of durum wheat using crop wild relative crosses across four targeted countries (Morocco, Ethiopia, Senegal and Lebanon). The culmination of the previous phase of BOLD project was highlighted by noteworthy achievements, including the successful participatory assessment of Moroccan farmers' preferences. This invaluable feedback informed strategic decisions and contributed to the release of six new drought-tolerant varieties of durum wheat and barley. These resilient varieties not only enhance agricultural productivity but also play a pivotal role in bolstering food sovereignty for smallholder farmers in the face of challenging environmental conditions, particularly drought stress. The collaborative efforts showcased in this presentation exemplify a successful integration of scientific advancements and local insights for sustainable and resilient agriculture.